Associations of Delay in Doctor Consultation With COVID-19 Related Fear, Attention to Information, and Fact-Checking - Lai, Agnes Yuen-Kwan; Sit, Shirley Man-Man; Wu, Socrates Yong-Da; Wang, Man-Ping; Wong, Bonny Yee-Man; Ho, Sai-Yin; Lam, Tai-Hing (Frontiers in Public Health, 2021)
Background: Delaying doctor consultation is harmful. Fear of COVID-19 leads to delays in seeking medical care at a time when pandemic information overflows. However, little is known about the role of COVID-19 related fear, attention to information, and fact-checking in such delay. Objective: Under the Hong Kong Jockey Club SMART Family-Link Project, we examined the associations of delay in doctor consultation amidst the pandemic with sociodemographic characteristics, COVID-19 related fear, attention to information, and fact-checking. Methods: We conducted a population-based online cross-sectional survey in May 2020 on Hong Kong Chinese adults. Respondents reported whether the pandemic caused any delay in doctor consultation (yes/no), level of COVID-19 related fear, attention to information and fact-checking (all on a scale of 0 to 10 and recoded into tertiles of low, moderate, high). Regression analyses were used to examine the associations of delay and fear with sociodemographic characteristics, attention and fact-checking, adjusting for covariates. Data were weighted by sex, age and education level of the population. Results: Of 4551 respondents (46.5% male, 59.7% aged over 45 years), 10.1% reported delay in doctor consultation. The mean score was 6.4 for fear, 8.0 for attention and 7.4 for fact-checking. Delay was more common in males and increased with age and fear. High versus low level of fear was associated with delay [adjusted odd ratios (AOR) 2.68, 95% confidence interval (CI) 2.08, 3.47]. Moderate level of fact-checking was negatively associated with delay (AOR 1.28, 95% CI 0.98, 1.67). Females reported greater fear and fear decreased with age. Fear increased with attention to information and decreased with fact-checking. Fear substantially mediated the association of delay with attention (96%) and fact-checking (30%). Conclusions: We have first shown that delay in doctor consultation increased with fear of COVID-19 and decreased with fact-checking amidst the pandemic. Fear also increased with attention to COVID-19 related information and decreased with fact-checking. Understanding these associations can help policymakers develop targeted communication and support to the public to reduce delayed doctor consultations and the associated COVID-19-related or unrelated morbidity and mortality in the community.